The Gathering Storm : Eduardo Frei's Revolution in Liberty and Chile's Cold War - Hurtado-Torres, Sebastián, 1982- (Book collections on Project MUSE., 2020)
"A new interpretation of the involvement of the United States in Chilean politics in the years of Eduardo Frei's Revolution in Liberty"--